Guy L. Hursch, Revised Ordinances and Rules of the City Council, of the City of Holton 1905, at 130, 134-35, § 19 (1905) (effective Aug. 8, 1888) - (:unkn) unknown (My University, 1888)
No. 169, § 19: Any person who shall, within this city, discharge any fire arms in any public place or in any street, alley or avenue, or any person who shall discharge any rockets, powder, fireworks or other dangerous combustible material in the streets, lots, grounds, alleys, or about or in the vicinity of any building shall, upon conviction thereof, be fined in any sum not exceeding one hundred dollars.§Provided, however, that the provisions of this section shall not extend to persons making a display of fireworks by permission of the mayor and council of this city and under the direct supervision of a committee appointed by the same.
Keywords: DISCHARGE